Human obesity and Arctic adaptation: epidemiological patterns, metabolic effects and evolutionary implications - Young, T (1994)
The objective of this dissertation is to investigate the occurrence, determinants and consequences of obesity among the Inuit people in the central Canadian Arctic, based on the Keewatin Health Assessment Study (KHAS), conducted during 1990/91 in 8 Inuit communities in the Northwest Territories (n=434 adults aged 18yr+). Data from three other surveys are included for comparison: (1) the 1190 Manitoba Heart Health Survey among 2200 predominantly Caucasian residents of the province of Manitoba; (2) the 1986-87 Northern Indian Chronic Disease Study among 704 Cree-Ojibwa Indians from Northern Ontario and Manitoba; and (3) the 1990-91 Chukotka Chronic Disease Survey among 362 Chuckchi and Inuit in coastal Chukotka in the Russian Far North. Judged by both body mass index and two skinfold thicknesses, obesity among the Inuit in the Keewatin region is as prevalent as it is in the general North American population. This is a new development over the past two or three decades, the result of rapidly changing physical activity, diet and other lifestyles. Obesity is more prevalent among women, among whom there is also a higher prevalence of central fat patterning. Age, education and non-smoking status (females only) are consistently identified as independent predictors of various obesity indices on multivariate analysis. While better educated men are more likely to be obese, the relationship is reversed in women, possibly due to the different sex roles and their associated stress levels in a rapidly acculturating and modernizing society. When different categories of obesity indices are compared, there is a consistent pattern of an increasing trend in blood pressure and one or more of the lipids but no significant change in glucose or insulin level. This observation distinguishes the Inuit and Chukchi from Caucasians and Amerindians. Even where a relationship exists, as with triglycerides and HDL-cholesterol, the magnitude of response is also lower among the Inuit. The differential effect of obesity on glucose, blood pressure and lipids in Inuit compared to non-Inuit suggests a type of selective insulin resistance, the underlying mechanism of obesity and several chronic diseases. The Inuit metabolism reflects their almost exclusive diet of fat and proteins. Apart from its public health importance, the study of Inuit obesity can shed some light into issues related to the peopling of the Americas: are the Inuit "exempt" from the "New World syndrome", and can the "thrifty genotype" explain the differential occurrence of diabetes among Arctic and Subarctic hunter-gatherers? It provides an opportunity to elucidate fundamental questions relating to the interaction of genetic and environmental factors in disease causation and distribution.